Seizure Freedom After Epilepsy Surgery and Higher Baseline Cognition are Associated with an Anti-Correlated Epilepsy Network. (16th November 2020) - Park, You J; Neal, Elliot; Di, Long; Finch, David A; Korneli, Ferdinand; Maciver, Stephanie; Schoenberg, Michael; Vale, Fernando L
Abstract: INTRODUCTION: One-third of patients experience recurrent seizures after epilepsy surgery, and an inadequate disconnection of the epilepsy network may be a contributing reason. Pre-operative network modeling may be a valuable tool that can improve resection targeting, network disconnection, and efficacy of epilepsy surgery. Brain regions positively correlated with the epileptogenic zone have been associated with seizure recurrence and cognitive impairment, but anti-correlated regions have not been as well studied. METHODS: Scalp EEG and rsfMRI were collected from 27 patients with unilateral temporal lobe epilepsy to map the hypothesized irritative zone and correlated regions to model the pre-operative epilepsy network. Using patients' rsfMRI, the anti-correlated epilepsy network was mapped by determining the correlation matrix for all the voxels with Pearson correlation values less than -0.4 with respect to the epileptogenic zone. Post-operative connectivity within the modeled network was determined by calculating the mean Pearson connectivity coefficient within the network when the same set of voxels were overlaid on the post-operative rsfMRI. Neuropsychological function was also assessed pre- and post-operatively and compared to the connectivity of the anti-correlated epilepsy network. RESULTS: The degree of connection within the anti-correlated epilepsy network was unrelated to that of the standard epilepsy network ( P = .214). Anti-correlated network synchronization was inversely related to network spread (R = −0.761, p < 0.001) and higher in patients who were seizure-free ( P = .026). Pre-operative anti-correlated epilepsy network synchronization was correlated with higher baseline verbal memory, logical memory, and executive function. CONCLUSION: Pre-operative anti-correlated network connectivity was associated with higher rates of post-operative seizure-freedom and higher pre-operative memory and executive function, suggesting that a highly connected anti-correlated epilepsy network may be used to predict who will benefit from surgery. These findings further support the use of non-invasive network mapping, including the anti-correlated epilepsy network, to predict surgical outcomes.